Collection Lags, Fiscal Revenue and Inflationary Financing : Empirical Evidence and Analysis - Choudhry, Nurun (IMF Working Papers; Working Paper ;, 1991)
The paper provides empirical evidence on collection lags in major categories of government revenue and analyzes the estimated revenue-eroding effects of inflation within the standard model of inflationary finance. The evidence indicates a wide variation in collection lags among the categories of revenues. The estimated erosion of real fiscal revenue, although varied in the sample countries, appears to have substantially offset gains from the inflation tax, thereby severely restricting the use of this form of taxation in generating resources.